Sebuah Tinjauan Literatur Sistematis atas Implementasi Key Performance Indicators - Indra Setiawan; Purba, Humiras Hardi (AGUSPATI Research Institute, 2020)
Management performance measurement based on Key Performance Indicators (KPIs) has been widely applied in any organization. This paper aims to identify Key Performance Indicators (KPIs) and classify them based on performance measurements to improve optimal management organizational performance. This research is based on a literature review of 50 journals based on performance management with the weight of Key Performance Indicators (KPIs) for the years 2011-2020. Performance measurement using this Key Performance Indicator can be implemented in many institutional organizations such as industry company sector, services, academics, hospitals, and government. KPIs can change behavior in an organization and provide results in broad contexts such as improving business results or driving improved operational performance. KPIs also help in implementing performance measurement on an ongoing basis. So that KPIs become a better way of managing the organization.